Diagnostics and Reliability of Pipeline Systems - Timashev, Sviatoslav; Bushinskaya, Anna (Topics in Safety, Risk, Reliability and Quality, 2016)
The book contains solutions to fundamental problems which arise due to the logic of development of specific branches of science, which are related to pipeline safety, but mainly are subordinate to the needs of pipeline transportation.          The book deploys important but not yet solved aspects of reliability and safety assurance of pipeline systems, which are vital aspects not only for the oil and gas industry and, in general, fuel and energy industries , but also to virtually all contemporary industries and technologies. The volume will be useful to specialists and experts in the field of diagnostics/ inspection, monitoring, reliability and safety of critical infrastructures. First and foremost, it will be useful to the decision making persons -operators of different types of pipelines, pipeline diagnostics/inspection vendors, and designers of in-line -inspection (ILI) tools, industrial and ecological safety specialists, as well as to researchers and graduate students.